PENERAPAN DAN SOSIALISASI PIPA RESAPAN HORIZONTAL PADA MUSLIMIN SCHOOL DI THAILAND - Yusuf, Faisal; Crista, Ngudi Hari; Paninggiran, Herman; Widorini, Trias; Azkiya, Safrina Dina; Adji, Dhimas Sasongko; Saputra, Andhika Rizal; Putri, Marsela Ragil; Prita, Prita (Politeknik Negeri Semarang, 2024)
This article presents the socialization and implementation of Horizontal Infiltration Pipes at Muslimin Schools in Thailand. The aim of this socialization is to introduce the research findings of Dr. Ir Edy Susilo, MT Lecturer at Semarang University, where using a simple pipe can have the ability to absorb runoff or flood water that is absorbed into the ground. In this socialization, participants consisting of teachers and students in carrying out community service activities showed that the training participants were able to properly know and understand knowledge in the field of piping and hydro which aims to be an alternative for storing water in the ground.